May–Thurner Syndrome in a 31-Year-Old Female with Chronic Deep Vein Thrombosis - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
MayThurner syndrome (MTS) also known as iliocaval compression, occurs as a result of left common iliac vein compression by the right iliac artery. The syndrome is characterised by persistent leg swelling, venous ulcer, deep-vein thrombosis (DVT) and pulmonary embolism. However, it is rarely diagnosed with one of the causes of DVT. We hereby present a 31-year-old woman with persistent left lower limb DVT caused by MTS.